FINANCIAL ANALYSIS OF NILEM FISH FARMING IN CIAMIS REGENCY, WEST JAVA PROVINCE - Sari Rachmawati; Ganjar Wiryati; Cheriel Dorathya Rengkung; Alifiah Tantri Pramadhian (Universitas Mataram, 2025)
Sustainability of aquaculture enterprises requires not only good technical cultivation practices but also robust financial feasibility analysis. This study aims to analyze the financial feasibility of Nilem (Osteochilus hasselti) farming in Ciamis Regency, West Java. The research was conducted in Cipaku Sub-district, with ten aquaculture farmers selected by purposive sampling. Financial feasibility was assessed using indicators: Revenue/Cost (R/C) ratio, Break-Even Point (BEP), Payback Period, and Return on Investment (ROI). The results showed an R/C Ratio of 2 (R/C > 1), indicating that every one rupiah of cost generated two rupiahs of revenue, hence the enterprise is operationally feasible. Sales of 13,175 fish yielded revenue of Rp 1,054,000, exceeding the BEP in unit (3,819 fish) and in rupiahs (Rp 305,362), illustrating that the operation has surpassed the break-even point and is profitable. The ROI was recorded at 16 % per production cycle. Based on these three indicators, it can be concluded that Nilem aquaculture in Ciamis Regency is financially feasible and profitable. For sustainability and business development, it is recommended to conduct sensitivity analyses on fluctuations in cost and price, as well as further studies on larger-scale operations to enhance both sustainability and efficiency.